Study guide: HBEC2403 Early Childhood Literature 1: International Folktales - Badzis, Mastura (Open University Malaysai (OUM), 2011)
This course is designed to enhance students’ understanding in early childhood literature and its practicability to children’s context. The course content will resolve around early childhood literature; its history, its characteristics, its relations to children and as a tool or promoting literacy and communicative process (listening, speaking, reading, writing). Emphasis will also be placed on quality environment that indirectly influence early childhood literature. It can be in the form such as arrangement of indoor/outdoor spaces as well as locating, panning, implementing and evaluating creative learning activities using a variety of methods and materials.